Segmented Reporting and its Changes as a Result of the Covid-19 Pandemic in the Construction and Real Estate Industry - Dynowska, Joanna; Krysztofiak, Katarzyna (Olsztyn Economic Journal, 2026)
This paper analyses the impact of the COVID-19 pandemic on segment reporting in the construction and real estate sector in Poland. The study includes an analysis of the financial statements of companies listed on the Warsaw Stock Exchange in 2019 and 2023. The study results indicate that the COVID-19 pandemic did not cause fundamental changes in the structure of the reported operating segments of the surveyed companies (segmentation by business line still dominates), but it reduced the scope of disclosed financial results. In some cases, a reduction in the number of reported segments was observed, which could be a response to changing market conditions. The study results highlight the flexibility of segment reporting and its ability to adapt to global crises. Although the pandemic did not lead to significant changes in accounting regulations, it forced the adaptation of management strategies to new economic realities.